Mammaglobin-A Expression Is Highly Specific for Tumors Derived from the Breast, the Female Genital Tract, and the Salivary Gland - Natalia Gorbokon; Patrick Timm; David Dum; Anne Menz; Franziska Büscheck; Cosima Völkel; Andrea Hinsch; Maximilian Lennartz; Andreas M Luebke; Claudia Hube-Magg; Christoph Fraune; Till Krech; et al. (Diagnostics, 2023)
Human mammaglobin-A (SCGB2A2) is a secretory protein with an unknown function that is used as a diagnostic marker for breast cancer. However, other tumors can also express mammaglobin-A. To comprehensively study patterns of mammaglobin-A expression, a tissue microarray containing 16,328 samples from 128 different tumor types as well as 608 samples of 76 different normal tissue types was analyzed using immunohistochemistry. Mammaglobin-A positivity was found in only a few normal tissues, including luminal cells of the breast as well as endocervical and endometrial glands. In tumor tissues, 37 of 128 tumor categories showed mamma-globin-A staining, 32 of which were derived from one of four organs: breast (6 tumor categories), endometrium (5 tumor categories), ovary (5 tumor categories), and salivary glands (16 tumor categories). Only five additional tumor types showed occasional weak mammaglobin positivity, including medullary thyroid cancer, teratoma of the testis, squamous cell carcinoma of the skin and pharynx, and prostatic adenocarcinoma. Among 1139 evaluable invasive breast carcinomas of no special type, low mammaglobin-A immunostaining was linked to high BRE grade (p = 0.0011), loss of estrogen and progesterone receptor expression (p < 0.0001 each), and triple-negative status (p < 0.0001) but not to patient survival. In endometrial cancer, mammaglobin-A loss was linked to an advanced tumor stage (p = 0.0198). Our data characterize mammaglobin-A as a highly specific marker for tumors derived from either the breast, female genitals, or salivary gland.